An interpretative structural modeling based network reconfiguration strategy for power systems. (February 2015) - Zhang, Can; Sun, Lei; Wen, Fushuan; Lin, Zhenzhi; Ledwich, Gerard; Xue, Yusheng
Highlights: A line importance evaluation method is proposed based on the contraction concept. ISM is employed to analyze the relationship among different factors. The generator to be restored is selected by maximizing the restoration benefit. The start-up sequence of generators and restoration paths are optimized together. Abstract: The network reconfiguration is an important stage of restoring a power system after a complete blackout or a local outage. Reasonable planning of the network reconfiguration procedure is essential for rapidly restoring the power system concerned. An approach for evaluating the importance of a line is first proposed based on the line contraction concept. Then, the interpretative structural modeling (ISM) is employed to analyze the relationship among the factors having impacts on the network reconfiguration. The security and speediness of restoring generating units are considered with priority, and a method is next proposed to select the generating unit to be restored by maximizing the restoration benefit with both the generation capacity of the restored generating unit and the importance of the line in the restoration path considered. Both the start-up sequence of generating units and the related restoration paths are optimized together in the proposed method, and in this way the shortcomings of separately solving these two issues in the existing methods are avoided. Finally, the New England 10-unit 39-bus power system and the Guangdong power system in South China are employed to demonstrate the basic features of the proposed method.